Is There any Seasonal Influence of Herpes Zoster? - Rahman, Md Habibur; Karim, Md Rezaul; Tauhid, Syed Ahsan; Das, Asit Ranjan; Sarkar, Sumitendra Kumar (Faridpur Medical College Journal, 2017)
Herpes zoster is a neurocutaneous disease caused by varicella zoster virus (VZV). It results from the reactivation of latent virus in dorsal root or cranial nerve cells following primary infection or vaccination as a consequence of waning of immunity. There may be a possible association between the occurrence of varicella infection and various environmental factors. So this study was designed to know the pattern of clinical presentation, seasonal variations and epidemiological factors of Herpes Zoster patients. A total of 172 Herpes Zoster out of 27979 patients of different skin diseases attending at Dhamrai Upazilla Hospital in Bangladesh were studied between March 2010 to June 2013. The frequency of occurrence of Herpes Zoster was 0.61%. Among the patients, 57.56% were male and 42.44% were female between the ages of 5 months to 90 years, with mean age 39 years. Nearly half of the patients (48.26%) were in between 30-59 years age. The patients were continued to report throughout the year with a surge in rainy season. Majority of the patients (65.70%) had thoracic dermatome followed by cervical and lumbar distribution, each of them 11%. A large-scale and prospective community based study is recommended to enrich the findings as well as a complete clinical and epidemiological picture of Herpes zoster in Bangladesh. Faridpur Med. Coll. J. Jan 2017;12(1): 14-17